2016
DOI: 10.22256/pubvet.v16n10.1319
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of branches and fruits of Jurema preta and bran and the diet of Santa Inês sheeps- A review

Abstract: Estudante de Graduação em Medicina Veterinária da UFCG/Patos-PB. ResumoA ovinocultura é uma atividade relevante em vários continentes, adaptando-se a uma grande variedade de climas. O Nordeste brasileiro é a região com o maior rebanho ovino do Brasil, porém a maior parte dos animais não tem padrão de raça definido e é criado extensivamente e sem práticas apropriadas de manejo alimentar, sanitário e reprodutivo. Além disto, a fartura de forragem nos quatro a cinco meses da estação úmida contrasta com a carência… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Due to these characteristics and its prevalence in the Brazilian semi-arid region, farmers have been using Mimosa tenuiflora hay as an alternative feed for sheep and goats. In a study conducted by Bandeira et al [1], the average values of crude protein (CP), neutral detergent fibers (NDF), and acid detergent fibers (ADF) in Mimosa tenuiflora hay were found to be 14.4%, 44.5%, and 29.5%, respectively, whereas the digestibility of dry matter (DM) varies between 40% and 60% depending on the physiological phase and plant part, as observed by Pereira Filho et al [2] and Cordão et al [3].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Due to these characteristics and its prevalence in the Brazilian semi-arid region, farmers have been using Mimosa tenuiflora hay as an alternative feed for sheep and goats. In a study conducted by Bandeira et al [1], the average values of crude protein (CP), neutral detergent fibers (NDF), and acid detergent fibers (ADF) in Mimosa tenuiflora hay were found to be 14.4%, 44.5%, and 29.5%, respectively, whereas the digestibility of dry matter (DM) varies between 40% and 60% depending on the physiological phase and plant part, as observed by Pereira Filho et al [2] and Cordão et al [3].…”
Section: Introductionmentioning
confidence: 73%
“…It is crucial to determine the appropriate level of tannin for each specific ruminant species and category to ensure optimal animal performance without compromising organic functions. Studies conducted by Cordão et al [3] and Bandeira et al [1] with hair lambs recommend tannin levels of up to 40 g per kg of dry matter (DM) in the diet. Similarly, [42] observed that hydration and milk production in dairy cows can be maintained by incorporating up to 4.3 g of tannins per kg of DM in the diet.…”
Section: Discussionmentioning
confidence: 99%